The effects of unconventional monetary policy announcements on equity market : Announcement effect on the euro area stock markets - Löövi, Teemu (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis analyses the effects of European Central Bank unconventional monetary policy on the stock market between Aug 2007 and Dec 2016. Moreover, I study reaction of individual stocks by exploiting company level data from German, French and Dutch markets. This allows for more comprehensive examination than using only index-level data. Reviewing transmission channels of monetary policy suggests examining possible heterogenous reaction the portfolio rebalance channel also causes and not only focus on the credit channel as is the case with previous research. I examine the general reaction of the stock market through Euro Stoxx TMI indices. Company level data is used to create portfolios that are characterised by the company attributes. To test the significance of the credit channel, company size and age represent the level of financial constraints. The company size, volatility and liquidity of the stock reflect investor preferences for stocks and test the significance of portfolio rebalance channel. I estimate the pass-through to indices and portfolios from euro area 10-year government bonds yield gap, 10-year government bond yields of the core countries, and Euribor futures rate. Identification through heteroskedasticity is used as an identification method. First, the pass-through form yield gap is very low and not statistically significant for any indices and portfolios tested. Measuring pass-through from bond yields and futures rate produces significant estimates for most indices and portfolios. Pass-through from bond yields and futures rate are similar for the subsample of zero lower bound, indicating the effect on yield curve was uniform. Second, relation of bond yields/futures rate and stock market is positive for period before zero lower bound. Thus, increase in yield curves of core countries led to positive aggregate stock market reaction. This relation changed to negative after closing of the gap in the euro area government bond yields. Third, portfolio tests show that larger companies with liquid stocks have strongest reaction to policy announcements. Company age seems to be significant only in bear market conditions, while stocks with extremely high or low volatilities have small to no reaction to policy news. Results of portfolio tests are not completely in line with previous research. I suspect this difference occurs because the portfolio rebalance channel may be more relevant with asset purchase type announcements than with conventional monetary policy announcements. Current literature offers rather complete picture of policy effects on aggregate stock market and financial markets in general. However, different transmission channels associated with the heterogenous reaction of stocks, or other financial assets, are still relevant topics for future research.